2019
DOI: 10.4014/jmb.1808.08026
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine and 1-Undecene Producing Pseudomonas chlororaphis subsp. aurantiaca Strain KNU17Pc1 for Growth Promotion and Disease Suppression in Korean Maize Cultivars

Abstract: In this study, strain KNU17Pc1 was tested for its antifungal activity against Rhizoctonia solani AG-1(IA), which causes banded leaf and sheath blight (BLSB) of maize. KNU17Pc1 was tested further for its broad-spectrum antifungal activity and in vitro plant growth promoting (PGP) traits. In addition, the in vivo effects of KNU17Pc1 on reduction of BLSB severity and seedling growth promotion of two maize cultivars under greenhouse conditions were investigated. On the basis of multilocus sequence analysis (MLSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…Our in vivo assays also showed that KNU-07 promoted the growth of pepper plants after inoculation into the soil. Strains of B. thuringiensis have been used to promote the growth of plants, and our findings are consistent with these reports [36][37][38]. Previous studies reported that PGPR strains possessing siderophore production play a great role in helping plants to acquire iron for plant growth [13].…”
Section: Discussionsupporting
confidence: 92%
“…Our in vivo assays also showed that KNU-07 promoted the growth of pepper plants after inoculation into the soil. Strains of B. thuringiensis have been used to promote the growth of plants, and our findings are consistent with these reports [36][37][38]. Previous studies reported that PGPR strains possessing siderophore production play a great role in helping plants to acquire iron for plant growth [13].…”
Section: Discussionsupporting
confidence: 92%
“…The antifungal activity of 1-undecene against R. solani AG-1(IA), which causes banded leaf and sheath blight (BLSB) of maize, has been reported (Tagele et al, 2019). The volatile methyl siloxane octamethylcyclotetrasiloxane (D4) has been reported to have antibacterial and antifungal activity (Lin et al, 2014) and was found in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…subsp. aurantiaca KNU17Pc1 [53] and P. chlororaphis O6 (unpublished) when isolates are grown on rich medium. Other VOCs detected in both O6 (unpublished) and M71 [46] isolates include S-containing compounds, such as hydrogen sulfide, dimethyl sulfide and methanethiol.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%